Soil Phosphorus Dynamics Across a Holocene Chronosequence of Aeolian Sand Dunes in a Hypermaritime Environment on Calvert Island, BC, Canada - Nelson, Lee-Ann; Cade-Menun, Barbara J.; Walker, Ian J.; Sanborn, Paul (Frontiers in Forests and Global Change, 2020)
Phosphorus (P) is an essential nutrient for plant growth, but soil P concentrations decline with increasing soil age. Phosphorus often limits tree growth within the hypermaritime Coastal Western Hemlock zone in British Columbia, Canada, particularly where parent material with low P concentrations have experienced rapid weathering. To sustainably manage forests in this region, more information is needed about changes in soil P concentrations and dynamics that occur with time. This study characterized the forms and abundance of soil and foliar P compounds using a soil chronosequence developed on aeolian sand dunes on Calvert Island and compared results to chronosequences in other locations. Eight time points were examined, from a modern foredune to a relict, stabilized dune (~10,760 years old). Soil horizons were analyzed for bulk density, pH, and concentrations of total carbon (C), nitrogen (N) and total P (TP), iron (Fe) and aluminum (Al), total organic P (Po), and Mehlich-extractable P and cations. For each site, P forms in L, H and organically-enriched mineral (M) horizons were characterized with solution 31P nuclear magnetic resonance spectroscopy (P-NMR), as were foliar samples from tree species spanning all age classes except the youngest dune. This chronosequence followed the Walker and Syers (1976) model, with an exponential decline in TP mass and a humped-shape curve in Po mass with increasing age. The L horizon had lower TP concentrations than foliage samples, but similar P forms. The H horizons had a greater proportion of DNA, phosphonates and nucleotides than the L horizon and increased proportions of myo- and scyllo-inositol hexakisphosphate (IHP) with increasing age. The mineral horizons had much lower TP concentrations than other horizons and increased proportions of IHP and DNA with increasing age, which were correlated to increased exchangeable and amorphous Al concentrations. In all sample types, the proportion of orthophosphate declined with increasing age. These results enhance knowledge of P cycling within hypermaritime soils, particularly the P decline that will occur with age. This will aid in the sustainable management of the low-productivity forests typical of these ecosystems.